Personal Social Responsibility Campaign for Helping Others in Facing COVID-19 Pandemic - Leila Mona Ganiem; Ibnu Hamad (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
As one can see, people who have tested positive for COVID-19 and self-isolated are at a risk of experiencing inconvenience such as stigma, lack of   support from the environment, loneliness, depression, and anxiety, which may increase premature mortality. They may save their lives if they receive greater attention and support, especially from the closest people in their community besides people who have got support from the community to recover faster from the virus. The act of kindness is a prosocial action in this form called personal social responsibility (PSR). The objectives of the study are to elaborate on the prosocial behavior of PSR and provide a campaign strategy for encouraging people to carry out PSR activities in their community as prosocial action or altruism to support COVID-19 sufferers, especially those who self-isolate and are infected by COVID-19. This study uses a systematic literature review as its method. Data was collected by searching and accessing relevant literature. The data was analysed based on a thematic and descriptive analysis of the selected literature. The study found that PSR plays a significant role in overcoming social burdens among citizens, including in dealing with the COVID-19 pandemic. To articulate the PSR Campaign, the researcher refer to communication strategies and social campaign models. Through the campaign, prosocial behaviors must generate in many terms of giving product, money, thought, time, or other forms of concern related to feelings.